PHYSICS MODEL MOVEMENT OF COVER STEEP SLOPES IN AMBON ISLAND MOLUCCAS - SOUISA - NIM: 30213013, MATHEUS
Investigation of landslide disaster in the region of Ambon Island Maluku is very important, because remembering from year to year the frequency of landslide disaster continues to increase. The landslide scattered throughout Ambon Island, where the most severe landslide on Ambon Island, which caused massive losses and claimed many lives were landslides in Kampung Booi, landslide in Amahusu, landslide in Erie and landslide in Negeri Lima. In this research, an integrated multidisciplinary approach involves field study, laboratory measurement, modeling, and analysis to determine the area of slip and slope safety factor in the landslide area in order to anticipate the occurrence of aftershocks. The study was conducted to reduce the mathematical release of slope / hill cover soil as landslide process to obtain the field collapse equation in the landslide by Mohr-Coulomb criterion approach. There is also a review of the landslide deterioration to determine the sliding mudslides mechanism due to dragging water until settling debris/sediment. The results showed that in four locations the study is still vulnerable to landslides following the occurrence of external disturbances that trigger with the safety factor range 0.87Ã‚Â–0.97. Areas that are under threat of high landslide are Sirimau, Nusaniwe, and Leihitu Subdistricts. To avoid and minimize the occurrence of aftershocks applied water toll model as prevention of landslides and slope erosion. The calculation results of the runout phase prediction (landslide length, landslide velocity and runout time) in four landslide locations are different, this difference depends on the measurement of the geometry parameter of the landslide slope face. Furthermore, the calculation of the settling rate of debris / sediment at each landslide location also varies, depending on the geometry of the slope, the viscosity or the drain of debris flow or the flow of water, as well as the local geological stratigraphy.